Improving student success with online embedded tutor support in first-year subjects. 'A practice report' - Kelly Linden; Sarah Teakel; Neil Van der Ploeg (Student success, 2022)
Institutional commitment to the student experience in the early stages of university has the greatest potential to exceed student expectations. The cross-institutional Embedded Tutors Program provides undergraduate students with access to subject content experts from 12 first-year subjects across a regional university. Tutors provide one-on-one draft assessment feedback in subjects with a large written assessment task. A total of 428 students attended 615 tutor sessions held online via Zoom. Students who met with a tutor had higher average assessment marks and cumulative subject marks than those students who did not attend a session. Feedback from students was positive, with 78% of students rating the tutor session "extremely helpful." This study provides evidence of the value of subject-specific draft assessment feedback for students in first-year subjects.